Hydroamination, Aminoboration, and Carboamination with Electrophilic Amination Reagents: Umpolung-Enabled Regio- and Stereoselective Synthesis of N‑Containing Molecules from Alkenes and Alkynes - Hirano, Koji; Miura, Masahiro (Journal of the American Chemical Society, 2022)
Nitrogen (N) is ubiquitously found in bioactive molecules, pharmaceutical agents, and organic functional materials. Accordingly, development of new C–N bond-forming catalysis has been one of the long-standing research subjects in synthetic organic chemistry. In this Perspective, recent advances in highly selective amination reactions with electrophilic amination reagents are described: by taking advantage of the concept of nitrogen umpolung, otherwise challenging aminofunctionalizations, such as hydroamination, aminoboration, and carboamination, of readily available feedstock-like alkenes and alkynes are possible, giving densely functionalized complex and often chiral alkylamines with high selectivity. The scope, limitations, and reaction mechanism are briefly summarized.